The Impact of Prior Abdominal Surgery on Complications of Abdominally Based Autologous Breast Reconstruction: A Systematic Review and Meta-Analysis - Bond, Evalina S.; Soteropulos, Carol E.; Yang, Qiuyu; Poore, Samuel O. (Journal of Reconstructive Microsurgery, 2021)
Background Approximately half of all patients presenting for autologous breast reconstruction have abdominal scars from prior surgery, the presence of which is considered by some a relative contraindication for abdominally based reconstruction. This meta-analysis examines the impact of prior abdominal surgery on the complication profile of breast reconstruction with abdominally based free tissue transfer.Methods Literature search was conducted using PubMed, Scopus, and Web of Science. Included studies examined patients with a history of prior abdominal surgery who then underwent abdominally based free flap breast reconstruction. Prior liposuction patients and those with atypical flap designs were excluded. The Newcastle-Ottawa Scale was used to assess study quality. Flap complications included total and partial flap loss, fat necrosis, infection, and reoperation. Donor-site complications included delayed wound healing, infection, seroma, hematoma, and abdominal wall morbidity (hernia, bulge, laxity). Relative risk and 95% confidence intervals (CIs) between groups were calculated. Forest plots, I2 statistic heterogeneity assessments, and publication bias funnel plots were produced. Publication bias was corrected with a trim-and-fill protocol. Overall effects were assessed by fixed-effects and random-effects models.Results After inclusion and exclusion criteria were applied, 16 articles were included for final review. These included 14 cohort and 2 case–control studies, with 1,656 (46.3%) patients and 2,236 (48.5%) flaps having undergone prior surgery. Meta-analysis showed patients with prior abdominal surgery were significantly more likely to experience donor-site delayed wound healing with a risk ratio of 1.27 (random 95% CI [1.00; 1.61]; I2= 4) after adjustment for publication bias. No other complications were statistically different between groups.Conclusion In patients with a history of prior abdominal surgery, abdominally based free tissue transfer is a safe and reliable option. Abdominal scars may slightly increase the risk of delayed donor-site wound healing, which can aid the surgeon in preoperative counseling.
Keywords: autologous breast reconstruction; DIEP flap; abdominal scar; prior abdominal surgery; cesarean section